RISK PERCEPTION OF SOCIALLY RESPONSIBLE INVESTORS IN MUSLIM COUNTRIES - Murtaza, Saqib; Rana, Hifza Mahmood; Noor, Fareeha; Sahdat, Madiha; Khan, Junaid (European Scientific Journal, ESJ, 2013)
From the evidence that socially responsible investment is an emerging concept in Muslim countries, we have developed a socio-demographic behavior based model. We have shown the direct effect of social factors (religion and family influence) and indirect effect of demographic factors (age, education and income) on investment choices through risk perception. Investors may be experienced in investment market but particularly in SRI investments of Muslim countries they will be new entrants. We have developed hypotheses from literature in our study regarding this concept of new entrants. In Pakistan, SRI investment is not prevailing but opportunities do exist. Pakistani firms can take the initiative by attracting SRI investments if firms develop more sophisticated CSR.